Analisis Pola Asuh dalam Meningkatkan Kemandirian Penyandang Autism Spectrum Disorder (ASD) di Rumah Layanan Autisme Semarang - Nada, Sania Qotrun; Sessiani, Lucky Ade; Wihartati, Wening; Asgyantini, Tri Hening; Hapsari, Estu Indri (Fisip UIN Sunan Gunung Djati Bandung, 2025)
Parenting has an important role in shaping the independence of children with Autism Spectrum Disorder (ASD). This study aims to analyze the parenting patterns applied at Rumah Layanan Autisme Semarang and its contribution to the development of children's independence with ASD. The research method used is descriptive qualitative with a case study approach. Data were collected through observation and interviews with five subjects of children with ASD and their parents or caregivers. The results showed that the parenting patterns applied varied, ranging from authoritarian, democratic, to a combination of both. Democratic parenting tends to be more effective in encouraging children's independence through a flexible and positive reinforcement-based approach. In contrast, authoritarian parenting that emphasizes strict discipline can hinder the development of children's initiative. Factors that influence the success of parenting include parents' level of understanding of ASD characteristics, consistency in parenting patterns, and a supportive environment. This research provides insights for parents, educators and practitioners in designing optimal parenting strategies to increase the independence of children with ASD.